Cadherin-13 Deficiency Increases Dorsal Raphe 5-HT Neuron Density and Prefrontal Cortex Innervation in the Mouse Brain - Forero, Andrea; Rivero, Olga; Wäldchen, Sina; Ku, Hsing-Ping; Kiser, Dominik P.; Gärtner, Yvonne; Pennington, Laura S.; Waider, Jonas; Gaspar, Patricia; Jansch, Charline; Edenhofer, Frank; Resink, Thérèse J.; et al. (Frontiers in Cellular Neuroscience, 2017)
Background: During early prenatal stages of brain development, serotonin (5-HT)-specific neurons migrate through somal translocation to form the raphe nuclei and subsequently begin to project to their target regions. The rostral cluster of cells, comprising the median and dorsal raphe (DR), innervates anterior regions of the brain, including the prefrontal cortex. Differential analysis of the mouse 5-HT system transcriptome identified enrichment of cell adhesion molecules in 5-HT neurons of the DR. One of these molecules, cadherin-13 (Cdh13) has been shown to play a role in cell migration, axon pathfinding and synaptogenesis. This study aimed to investigate the contribution of Cdh13 to the development of the murine brain 5-HT system. Methods: For detection of Cdh13 and components of the 5-HT system at different embryonic developmental stages of the mouse brain, we employed immunofluorescence protocols and imaging techniques, including epifluorescence, confocal and structured illumination microscopy. The consequence of CDH13 loss-of-function mutations on brain 5-HT system development was explored in a mouse model of Cdh13 deficiency. Results: Our data show that in murine embryonic brain Cdh13 is strongly expressed on 5-HT specific neurons of the DR and in radial glial cells (RGCs), which are critically involved in regulation of neuronal migration. We observed that 5-HT neurons are intertwined with these RGCs, suggesting that these neurons undergo RGC-guided migration. Cdh13 is present at points of intersection between these two cell types. Compared to wildtype controls, Cdh13-deficient mouse embryos display increased cell densities in the DR at E13.5, E17.5 and adulthood, and higher serotonergic innervation of the prefrontal cortex at E17.5. Conclusion: Our findings provide evidence for a role of CDH13 in the development of the serotonergic system in early embryonic stages. Specifically, we indicate that CDH13 deficiency affects the cell density of the developing DR and the posterior innervation of the PFC, and therefore might be involved in the migration, axonal outgrowth and terminal target finding of DR 5-HT neurons. Dysregulation of CDH13 expression may thus contribute to alterations in this system of neurotransmission, impacting cognitive function, which is frequently impaired in neurodevelopmental disorders including attention-deficit/hyperactivity and autism spectrum disorders.